Agonism in education: a systematic scoping review and discussion of its educational potential. Issue 5 (29th July 2022) - Koutsouris, George; Stentiford, Lauren; Benham-Clarke, Simon; Hall, David
ABSTRACT: Within political philosophy and particularly in the work of Chantal Mouffe and Hannah Arendt, "agonism" has been described as representing the notion of being able to challenge and dissent in a productive way. However, little is known about how agonism is used in the educational literature, other than some applications relevant to democratic education. This paper considers the use of agonism in the educational literature drawing on the findings of a systematic scoping review exploring how it has been used in the context of education. Five databases were searched for literature published using agonism within the context of education to map the existing body of work in a systematic fashion, and to explore how agonism has been differently conceptualised and utilised by researchers in the field of education. The findings suggest that there have been a range of attempts to apply agonistic principles in different educational sub-fields (including, citizenship education, early years education, initial teacher training, arts education and international education), and different interpretations of such principles into education based on different philosophical underpinnings (dissociative and associative approaches). As agonism is mostly explored in a theoretical way, we also discuss the potential of abstract theoretical agonistic principles from different philosophical traditions to be translated into meaningful practical applications for education in order to inform curriculum development, infuse democratic principles into classroom practice, and help to negotiate deep-running tensions amongst key stakeholders in education.